The Flirtations Among the Arts: Virginia Woolf’s Essays on Literature and Visual Culture - Azerêdo, Genilda (Aletria: Revista de Estudos de Literatura, 2025)
The aim of this text is to discuss three essays and a short story by Virginia Woolf on the dialogue between literature and the visual arts: “Pictures” (1925), “The Cinema” (1926), “Three Pictures” (1929), and “Walter Sickert” (1934). “Three Pictures” appears classified as an essay in Leonard Woolf’s organized edition The Death of the Moth and Other Essays (1942), and as a short story in The Complete Shorter Fiction of Virginia Woolf (1989), organized by Susan Dick. This aspect calls one’s attention to how Woolf uses creative strategies in her essays, thus blurring the boundaries between fiction and nonfiction. The discussion will highlight Woolf’s knowledge of visual art and culture so as to show, in the analysis of “Three Pictures”, the visual potential of the short story in dialogue with her critical principles.